Reaching LDL-C Goals Using Nudges: A Review of Literatures - Reagan F. Cabahug (New Horizons in Medicine and Medical Research Vol. 5, 2022)
To review literatures and analyse how nudges can help a physician attain patients’ LDL-C goals. Reduction in coronary events rates in high-risk patients is workable by modifying cardiovascular risk factors. Coronary heart disease is the leading cause of death in the United States and most European countries (CHD). The primary risk factor for coronary artery disease is hypercholesterolemia. High-density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) are both significant risk factors for coronary heart disease (CHD). Hydroxymethylglutaryl-CoA (HMG-Co-A) inhibitors are the most effective treatment for lowering LDL-C levels and, as a result, lowering cardiovascular death and morbidity. A nudge occurs when a choice architecture is designed to predictably control behaviour without limiting an individual’s choice. The direction and force of a nudge should be consistent with professional standards in order for it to be effective. The article described how the actions of patients and physicians contributed to the rising prevalence of cardiovascular diseases. Nudges, whether digital or manual (using post-its), can be effective in persuading physicians to be proactive and in increasing patients’ adherence to therapy. In order to achieve these objectives, trust between the patient and the physician is essential. Nudges can be an effective management tool for guiding correct behaviour among healthcare providers. The strategy is to persuade doctors that they are useful rather than annoying or controlling noodges.